A dual channel sulphur-containing macrocycle functionalised BODIPY probe for the detection of Hg(II) in mixed aqueous solution - Presti, Maria Lo (2018)
We report herein the synthesis and chromo-fluorogenic behaviour of a new probe 1 containing a boron-dipirromethene (BODIPY) unit electronically connected with a dithia-dioxa-aza macrocycle. Acetonitrile and water-acetonitrile 95:5 v/v solutions of the probe showed an ICT band in the visible zone and are nearly non-emissive. When acetonitrile was used as solvent, addition of Hg(II) and trivalent metal cations induced an hypsochromic shift of the absorption band and moderate emission enhancements. A highly selective response was obtained when using competitive media such as wateracetonitrile 95:5 v/v. In this case only Hg(II) induced a hypsochromic shift of the absorption band and a marked emission enhancement.